Pengaruh Perbedaan Jenis Pakan terhadap Kandungan Albumin dan Kelangsungan Hidup Ikan Gabus (Channa striata) - Muhammad Briliandar Saputra; Ade Dwi Sasanti; Yulisman Yulisman (Seminar Nasional Lahan Suboptimal, 2018)
Saputra et al, 2019. Effect of Different Types of Feed on Albumin Content and Survival of Snakehead Fish (Channa striata). pp. 394-401. Albumin plays an important role in maintaining plasma osmotic pressure and helps host recovery process due to a disease caused by a lack of blood protein. The availability of blood protein in sufficient quantities can help maintain fish health performance. Healthy fish produce high survival values. This study was conducted to determine the effect of different types of feed given to survival and albumin levels of snakehead fish. The treatment given in the form of P1 snakehead fish was given commercial pellets with 32% protein, P2 snakehead fish was given commercial pellets with 32% protein plus 3.5% black cumin and P3 snakehead fish was fed in the form of fresh water and sea water trash paste in comparison 1: 1. Fish are kept in hapa in concrete ponds for 30 days. Feeding is carried out three times a day at satiation. Fish maintenance was carried out at the Laboratorium Kolam Percobaan Faculty of Agriculture while measuring albumin levels was carried out at the Laboratorium Bioproses Faculty of Engineering, Srwijaya University. The study lasted from May to July 2018. The results of measurements of albumin levels of snakehead fish were found to produce P3 treatment with the highest average addition of albumin levels of 0.025 mg / ml, while the average addition of the lowest albumin levels was found in fish fed P1 treatment (0.015 mg / ml). The snakehead fish treated with P2 had an average addition of albumin of 0.019 mg / ml. The highest survival rate was found in fish in P3 which was 80%. The snakehead fish in treatment P1 and P2 have average survival values of 72.5% and 73.75%, respectively. The results showed that differences in feed did not significantly affect albumin levels and has significantly affect fish survival rate.